Application of alvarado scoring system in diagnosis of acute appendicitis (Sirte Journal of Medical Sciences, 2022)
Acute appendicitis is a common cause of abdominal pain and can be difficult to diagnose, especially during the early stages. There is still appreciable morbidity and occasionally mortality which may be related to failure of making an early diagnosis (1) As a result of their concern about these surgeons create for themselves 'a surgical security zone which allows them to accept a 15-30% negative laparotomy rate with impunity (2), Although various aids exist to facilitate more accurate diagnosis and reduce the rate of negative appendectomy, many are complex.Whereas simple scoring systems have been available for some time, they have not been widely tested. The aim of this study was conducted to assess one of these scoring systems which was described by Alvarado in 19851(1), by comparing it’s to the histopathology results of operated patients. This retrospective study of consecutive patients admitted to surgical ward at Benghazi Aljala hospital with suspicion of having acute appendicitis during the period of January 2008 to January 2010. The Alvarado scoring system was computed from admission notes and records correlated with histopathology, all cases with insufficient data or no histopathology result were excluded from the study Out of 153 patients 90 underwent appendectomy with the intention to treat appendicitis and dianosis was confirmed in 80 patients. Reliability of the system was assessed by calculating negative appendectomy rate and positive predictive value which was 85%, and the normal appendectomy frequency was 12%. Alvarado scoring system is easy, cheap, and useful tool in preoperative diagnosis of acute appendicitis and can work effectively in routine practice
Keywords: Acute Appendicitis; Appendectomy; Alvarado score